Determination of industrial buildings safety level under influence of aggressive industrial environment - Бакулін, Є.А. (Proceedings of National Aviation University (archive), 2005)
The analyses of normative documents currently in force, which determine the safety level of industrial buildings (constructions), that work under influence of aggressive industrial environment, was made. There was proposed a system of reliability indexes improvement for industrial object, which are under influence of aggressive forces, to raise their exploitation safety.